(untitled) (Journal of Asian Development Studies, 2024)
Many international legislation, public education campaigns, and legal action programs have been launched in response to the United Nations’ recognition of gender-based violence against women as a pressing global health and development concern. This article discusses new conceptual frameworks, methodological problems, and selected research findings to guide these endeavours. Recent research has shown links between sexuality, gender, power, and intimate violence in a variety of nations, and this article reviews such studies. Further, it draws attention to cultural elements—like media depictions of sex and violence—that can make women more susceptible to abuse. Unwanted pregnancies and abortions are just two of the many harmful behavioral, emotional, and physical health outcomes of victimization that are discussed in the article. More research is urgently needed to fill gaps in our knowledge about gender-based violence, its dynamics, and its impacts, particularly the role of the media, as well as to explain why different forms of violence have different consequences in different cultural settings.